POJEDINAČAN UTICAJ RADA RUKU I NOGU NA BRZINU PLIVANJA 50 METARA KRAUL KOD DEČAKA UZRASTA 15 I 16 GODINA - Goran Dimitrić; Borislav Obradović; Tijana Krsmanović; Milan Šolaja; Ivan Grujić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
In aim of confirming relations betwen swimming 50m crowl with arms only, swimming 50m crowl with legs only and 50m crowl swimming, a transversal research was carried out on 17 male swimmers aged 15-16. Criteria on this research was 50m crowl swimming - 50mK and predictor variables were: swimming 50m crowl with arms only - 50mRK, swimming 50m crowl with legs only - 50mNK. Regression analisys shows that swimming 50m crowl with legs only significantly correlate with 50m crowl swimming for this sample.